Psycoeducation of the Resilience of the Family of Patients with Mental Disorders in Overcoming Psychosocial Problems in the Transition of the Covid-19 Pandemic in the Region Buleleng Regency of Bali - Eka Lutfiatus Solehah; Nyoman Sri Ariantini (Universitas STRADA Indonesia, 2022)
Background: The Covid-19 pandemic affects all aspects of human life, physically, economically and psychosocially. This pandemic situation also affects the mental state of the families of ODGJ patients. This situation not only threatens overall health but also threatens the resilience of the family in dealing with the situation. Purpose: The study was to determine the effect of psychoeducation on the resilience of families of patients with mental disorders in overcoming psychosocial problems during the transition period of the COVID-19 pandemic in the Buleleng-Bali Regency area.Methods: The methods uses a true experiment using a one group pre-posttest approach. This research activity was carried out in two stages, namely field activities and activities to provide counseling and education about ODGJ care during the transition period.Results: This study indicate that before being given psychoeducation to families of ODGJ sufferers, most of the family toughness was in the less category as many as 57 respondents (57%) and after being given psychoeducation the family was mostly in the good toughness category as many as 67 respondents (67%). The results of the paired T test show the value of = 0.000 with = 0.05. The results of this test show that the value of < then H1 is accepted, meaning that there is an influence of psychoeducation on the resilience of the family of ODGJ patients in Overcoming Psychosocial Problems During the Transition Period of the Covid-19 Pandemic in the Buleleng Regency –Bali.Conclusion: Providing psychoeducation can help families become more resilient in dealing with psychosocial problems in treating DOGJ patients during the transition period of the COVID-19 pandemic.